Physician specialization and the quality of care for human immunodeficiency virus infection. - Landon, Bruce E; Wilson, Ira B; McInnes, Keith; Landrum, Mary Beth; Hirschhorn, Lisa R; Marsden, Peter V; Cleary, Paul D (Archives of internal medicine, 2005)
There is debate over the types of physicians who should treat patients with complex chronic medical conditions such as human immunodeficiency virus (HIV) infection. We sought to assess the relationship between specialty training and expertise and the quality of care delivered to patients with HIV infection.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Clinical Competence; Education, Continuing; Family Practice; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Primary Health Care; Quality Assurance, Health Care; Referral and Consultation; Regression Analysis; Retrospective Studies; United States